Original papersFacial skin cancers: general information and an overview of treatment methods - Witmanowski, Henryk; Lewandowicz, Edward; Sobieszek, Daria; Rykała, Jan; Łuczkowska, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Malignant tumors of the skin are the most common human cancers. Among them facial skin cancers form a sizable group. In recent years there has been a dynamic increase in morbidity. They are characterized by local invasiveness, they infiltrate the surrounding tissues, destroy adjacent structures and lead to significant loss of tissue, which represent a serious therapeutic problem as they are reported in advanced stages of development, and after surgery there are extensive losses of disrupting the aesthetics and function of the face. The most common tumor is basal-cell carcinoma (BCC), another is squamous cell carcinoma (SCC). In available bibliography there is no clear information about the standards of treatment of this type of cancer is observed, which led us to try to present basic information about facial skin cancers, their morphological and histological forms, and the routine treatment depending on location. Aim : The paper presents the current knowledge on non-melanoma cancers of the face, the algorithm according to the primary lesion location and the related therapeutic options. It also presents the possibility of reconstruction of tissue defects, depending on the location of the change on the basis of selected patients treated at the Department of Plastic, Reconstructive and Aesthetic Surgery, Medical University of Lodz. Material and methods : In the Clinic of Plastic, Reconstructive and Aesthetic Surgery, Medical University of Lodz in the years 1998-2008, 398 patients were treated because of non-melanoma skin cancers. Results: The method of surgical treatment depended on the type of cancer, its stage and location. In the case of changes located on the face, in the advancement of T1 (T1N0M0), a surgical excision with local plastics was introduced, in other cases – local flaps or skin grafts was applied. Conclusions : Despite enormous progress in medical science, surgery remains the method of choice in treating facial cancers. Only the primary cut and the suitable technique of plastic surgery, selected individually for each patient provides satisfactory results.